O contato português-pomerano na produção dos grupos [Cr] e [rC] : o caso das vogais suarabácticas - Silva, Felipe Bilharva da (2019)
The present work investigates svarabhakti, a short-duration vocalic element that occurs within consonantal clusters in languages such as Portuguese, normally showing similar vowel quality to that of syllable-nuclear vowel. Based on a gestural approach (BROWMAN; GOLDSTEIN, 1986; 1989; 1992) of the phenomenon, we intend to evaluate svarabhaktic vowels behavior in Portuguese clusters [Cɾ] and [ɾC] produced by bilingual women ‒ speakers of Portuguese and Pomeranian ‒ in the city of São Lourenço do Sul, in the state of Rio Grande do Sul. To do so, we analyze the productions of ten subjects, aged above 42 years, divided into two groups: bilinguals, formed by five participants born and living in São Lourenço do Sul city, who have Pomeranian as dominant language; monolinguals, formed by five participants living in the urban area of Pelotas, who do not speak in their everyday life other language than Portuguese. For the data collect, three experiments were designed. In the first experiment, participants observed five images, taken from the book Avaliação Fonológica da Criança (YAVAS; HERNANDORENA; LAMPRECHT, 1991), and were instructed to produce the largest number of objects they could find. In the second experiment, participants observed isolated pictures on a laptop screen and were instructed to say their names in the carrier sentence Digo ______ cada vez ‒ I say _____ each time. In the last experiment, participants were asked to read the orthographic representation of the same words presented in the second experiment, also in the carrier sentence. Audio data were collected using a microphone Zoom H4N and treated acoustically using Praat software (BOERSMA & WEENINK, 2016), 6.0.28 version. The statistical analysis was performed with SPSS Statistics software, version 20.0. The results showed a high frequency of svarabhaktic vowels in the productions of the two groups, although the bilinguals showed significantly fewer cases of such phenomenon. Svarabhaktic vowels durations were affected by the variables experiment, syllabic position, voicing and constriction location of the consonant adjacent to tap, stress and nuclear vowel. In bilingual production, longer svarabhaktic vowels were found in the initial position of the syllable, which may indicate a slower gestural coordination between consonantal gesture and tap’s alveolar gesture. Furthermore, bilingual participants produced significantly fewer number of taps in post-vocalic position, producing in that position rhotic variants such as trills, unvoiced alveolo-palatal fricatives and alveolar approximants, which can be motivated by phonotactic pattern of Pomeranian, in which there is no tap in final-syllabic position.. Finally, we conclude that the longest svarabhaktic vowels in the Pomeranian are the consequence of language-specific timing in the gestural organization of the consonant groups, which is reflected in the speech of bilingual participants.